-6(x+7)=-90

Simple and best practice solution for -6(x+7)=-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+7)=-90 equation:


Simplifying
-6(x + 7) = -90

Reorder the terms:
-6(7 + x) = -90
(7 * -6 + x * -6) = -90
(-42 + -6x) = -90

Solving
-42 + -6x = -90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + -6x = -90 + 42

Combine like terms: -42 + 42 = 0
0 + -6x = -90 + 42
-6x = -90 + 42

Combine like terms: -90 + 42 = -48
-6x = -48

Divide each side by '-6'.
x = 8

Simplifying
x = 8

See similar equations:

| 17-4*n=11+2*n | | 6/8=64 | | 3x-17y=11 | | 7x-3x-(10x+2)=5+x | | 12t^2-17t=5 | | 5+8n=50+.5n | | 2x+5y=6.25 | | 17-4n=11+2n | | 15x-4=3x+8 | | 7b+6=22 | | 4(6n-1)=164 | | 2x/9x-7 | | (12x+7)=(30x-4) | | 5a+9y=17 | | X^2-576=0 | | 1/5x+y=30 | | -28=-7x-2(-5x+23) | | 4(2-y)+3y=3(y-4) | | 16-8a=2a | | -11m+1=-10m+18 | | 8(7n-4)=-144 | | 8-n=3(2n-4) | | -11m+1=-10+18 | | -1/2(8x+2)+1/5(35x+10) | | 4b-7=20+4b | | (4u-5)(3+u)=0 | | 6b^2+23=11 | | 40/4=5x+2(-4x) | | 5/4(x+2)=3 | | 5w+41=3(w+9) | | 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 |

Equations solver categories